Numerical Dominance and Phylotype Diversity of Marine Rhodobacter Species during Early Colonization of Submerged Surfaces in Coastal Marine Waters as Determined by 16S Ribosomal DNA Sequence Analysis and Fluorescence In Situ Hybridization - Dang, Hongyue (American Society for Microbiology, 2002)
Early stages of surface colonization in coastal marine waters appear to be dominated by the marine Rhodobacter group of the α subdivision of the division Proteobacteria (α-Proteobacteria). However, the quantitative contribution of this group to primary surface colonization has not been determined. In this study, glass microscope slides were incubated in a salt marsh tidal creek for 3 or 6 days. Colonizing bacteria on the slides were examined by fluorescence in situ hybridization by employing DNA probes targeting 16S or 23S rRNA to identify specific phylogenetic groups. Confocal laser scanning microscopy was then used to quantify and track the dynamics of bacterial primary colonists during the early stages of surface colonization and growth. More than 60% of the surface-colonizing bacteria detectable by fluorescence staining (Yo-Pro-1) could also be detected with the Bacteria domain probe EUB338. Archaea were not detected on the surfaces and did not appear to participate in surface colonization. Of the three subdivisions of the Proteobacteria examined, the α-Proteobacteria were the most abundant surface-colonizing organisms. More than 28% of the total bacterial cells and more than 40% of the cells detected by EUB338 on the surfaces were affiliated with the marine Rhodobacter group. Bacterial abundance increased significantly on the surfaces during short-term incubation, mainly due to the growth of the marine Rhodobacter group organisms. These results demonstrated the quantitative importance of the marine Rhodobacter group in colonization of surfaces in salt marsh waters and confirmed that at least during the early stages of colonization, this group dominated the surface-colonizing bacterial assemblage.